Biomechanical analysis on archery athletes - Nur Syazwani, Mohd Noor (2013)
Biomechanical is the most important matter in analysis the human movement. In sport, Biomechanical analysis becomes crucial in order to get the best practice to make sure there are no injury occurs during training. This study will focus on Biomechanical analysis to the archery athletes. From this research, the best position of archers elbow was obtained and the best practice in archery is proposed in order to reduce the force on muscle. When the athletes used the incorrect elbow position, the muscle force will increase and the muscle will becomes fatigue. The archery game required repeat action. When the athletes need to repeat the same movement, the muscle will become fatigue easily and will give bad effect to the archer performance. For this present study, the experiment was run together with archery athletes from Majlis Sukan Negeri Terengganu (MSNT). The athletes were categorized to elite, intermediate and beginner. The comparison was made between the athletes and differentiates between genders. From the experiment, the elbow positions of the archers were observed and compare the muscle activation of the archers from the EMG signal. Most of the athletes unable to get the same peak EMG signal due to incorrect position of elbow and muscle fatigue. From the EMG signal obtained from the experiment prove that the most active muscle is deltoid muscle which is shoulder muscle. Basically, when the muscle activation is higher, the muscle force produced also will be higher as muscle force and muscle activation is assumed to be linear.